Quantification of the economic value of the recreational function of forests in the territory of Městské lesy Hradec Králové a.s. - David Březina; Jakub Michal; Zdeněk Adamec; Jana Burdová (Journal of Forest Science, 2019)
This article aims at the valuation of the potential and economic significance of the recreational ecosystem services of forests. The research was conducted in the area of Městské lesy Hradec Králové a.s. in 2018. A part of the questionnaire survey assessed by means of statistical analysis was based on the travel cost method and the contingent valuation method, which investigate the respondents' willingness to pay for services resulting from the recreational ecosystem service of forests. The research specifically dealt with the visitors' willingness to pay for the services resulting from the use of forest logging roads, forest clearings, and small structures of forest infrastructure. The questionnaires were created using foreign publications and case studies. The findings of the questionnaire survey indicated that visitors prevailingly believed that the recreational service provided by the area of interest should not be chargeable. The reason for this opinion was mainly the fact that the visitors perceive the forests in the territory of Městské lesy Hradec Králové a.s. as public goods, hence the access to them should be free of charge.